Colorectal cancer screening: Understanding the health literacy needs of hispanic rural residents - Wittich, Angelina R. (AIMS Public Health, 2019)
PURPOSE: Hispanics residing in rural areas are among those who are least likely to be screened for colorectal cancer (CRC) and more likely to present with late stage CRC than other racial or ethnic groups. We conducted a pilot study utilizing a mixed-method approach to explore perceptions of CRC and CRC screening among Hispanic adults residing in South Texas rural communities and to identify health literacy needs associated with CRC screening uptake. METHODS: A convenience sample of 58 participants, aged 35–65, were recruited to complete questionnaires and participate in focus groups, ranging in size from 4 to 13 participants. Six focus groups were conducted across 3 adjacent rural counties. A semi-structured moderator's guide was designed to elicit discussion about participants' experiences, knowledge, and perceptions of CRC and CRC screening. FINDINGS: Lack of knowledge of CRC and CRC screening as cancer prevention was a common theme across focus groups. A majority, 59%, reported never been screened. Thirty-nine percent reported they had been screened for colon cancer and 5% reported they did not know if they had been screened. Participants with lower educational levels perceived themselves at high risk for developing CRC polyps, would not want to know if they had CRC, and if they did have CRC, would not want to know until the very end. Limited information about CRC and CRC screening, a lack of specialized providers, limited transportation assistance, and compromised personal privacy in small-town medical facilities were perceived to be barriers to CRC screening. CONCLUSIONS: Low screening rates persist among rural Hispanics. Improving CRC screening literacy and addressing factors unique to rural Hispanics may be a beneficial strategy for reducing screening disparities in this at-risk population.